2014
DOI: 10.1039/c3nj01525d
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photocatalytic and electrochemical properties of Au nanoparticles supported TiO2 microspheres

Abstract: Au/TiO 2 composites were synthesized by a two-step hydrothermal approach and their photocatalytic and electrochemical properties were investigated. It is found that Au/TiO 2 composites with a large specific surface area, stability and catalytic activity of Au nanoparticles (NPs) demonstrate enhanced photocatalytic activity compared to pure TiO 2 microspheres. Furthermore, the electrochemical properties of the Au/TiO 2 composite electrode demonstrate its ability to electrocatalyze the oxidation of hydrogen pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 46 publications
2
12
0
1
Order By: Relevance
“…14 Among the several methods, photocatalysis is considered to be one of the most promising technology because of its simplicity, low cost, and relatively high efficiency. 1,5 In this context, the design and fabrication of new materials similar to polymer composites for the removal of organic dyes is a matter of great practical importance. Polymers consisting of inorganic nanoparticles embedded in a transparent host matrix have the ability to fabricate unique properties such as optical, thermal, and high dielectric constant properties for precise applications such as sensors, photoelectric conversion, and photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…14 Among the several methods, photocatalysis is considered to be one of the most promising technology because of its simplicity, low cost, and relatively high efficiency. 1,5 In this context, the design and fabrication of new materials similar to polymer composites for the removal of organic dyes is a matter of great practical importance. Polymers consisting of inorganic nanoparticles embedded in a transparent host matrix have the ability to fabricate unique properties such as optical, thermal, and high dielectric constant properties for precise applications such as sensors, photoelectric conversion, and photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a few studies have reported the synthesis of Pt NPs on high surface area Al 2 O 3 12 13 . However, for electrochemical systems, the NPs should be deposited on conductive materials, such as high surface area carbon materials, carbon nanotubes (CNT), and semiconducting materials (TiO 2 ) 14 15 16 .…”
mentioning
confidence: 99%
“…The results were compared to the activities of the following three semiconductor materials: (i) the commercial anatase TiO 2 from Sigma-Aldrich (99% anatase, 325 mesh); (ii) the commercial rutile TiO 2 from Sigma-Aldrich; and (iii) a TiO 2 anatase form doped with Au(0) NPs, following the same procedure as for Rh(0) NPs. This Au(0) NPs@TiO 2 nanocomposite, with 0.1 wt.% metal loading, was evaluated as a reference, since gold NP-loaded TiO 2 materials have already proved their efficiency in the photocatalytic degradation of various pollutants [62,63], owing to their strong visible light absorption, due to localized surface plasmon resonance [64,65]. The aim of this study was to check the effect of rhodium nanospecies on the photoactivity of TiO 2 support, and to compare the obtained results to Au doping.…”
Section: Resultsmentioning
confidence: 99%